Determination Spatial Location of Regional Landslide Using GIS - Zulkafly, Muhammad Hafiz (IRC, 2016)
In Malaysia, the main trigger factor of a landslide is rainfall. Most of the occurrences landslide cases in Malaysia, happen during rainfall. Therefore, it is important to identify those landslide area to minimize the destruction cause by landslide. By developing landslide hazard map could potentially minimize the destruction. This research was conducted on Murum reservoir of Murum River, which is in the uppermost part of the Rajang River basin for the Landslide Hazard Assessment (LHA). Therefore, Kriging interpolation method was used in Geographical Information System (GIS) with rainfall information obtained from rainfall station gauges